Mast cells selectively produce inflammatory mediators and impact the early response to Chlamydia reproductive tract infection - Mayavannan, Animamalar; Shantz, Emily; Haidl, Ian D.; Wang, Jun; Marshall, Jean S. (Frontiers in Immunology, 2023)
Introduction Chlamydia trachomatis (C. trachomatis) is a Gram-negative obligate intracellular bacterium that causes reproductive tract complications in women, including ectopic pregnancies and tubal factor infertility. We hypothesized that mast cells, which are common at mucosal barriers, may contribute to responses to Chlamydia infection and aimed to define human mast cell responses to C. trachomatis. Methods Human cord blood-derived mast cells (CBMCs) were exposed to C. trachomatis to assess bacterial uptake, mast cell degranulation, gene expression, and production of inflammatory mediators. The role of formyl peptide receptors and Toll-like receptor 2 (TLR2) were investigated using pharmacological inhibitors and soluble TLR2. Mast cell-deficient mice and littermate controls were used to examine the in vivo role of mast cells in influencing the immune response to Chlamydia infection in the female reproductive tract. Results C. trachomatis bacteria were taken up by human mast cells but did not replicate efficiently inside CBMCs. C. trachomatis-activated mast cells did not degranulate but maintained viability and exhibited cellular activation with homotypic aggregation and upregulation of ICAM-1. However, they significantly enhanced the gene expression of IL1B, CCL3, NFKB1, CXCL8, and IL6. Inflammatory mediators were produced, including TNF, IL-1β, IL-1RA, IL-6, GM-CSF, IL-23, CCL3, CCL5, and CXCL8. Endocytic blockade resulted in reduced gene expression of IL6, IL1B, and CCL3, suggesting C. trachomatis induced mast cell activation in both extracellular and intracellular locations. The IL-6 response to C. trachomatis was reduced when CBMCs were treated with C. trachomatis coated with soluble TLR2. Mast cells derived from TLR2-deficient mice also demonstrated a reduced IL-6 response to C. muridarum. Five days following C. muridarum infection, mast cell-deficient mice showed attenuated CXCL2 production and significantly reduced numbers of neutrophils, eosinophils, and B cells in the reproductive tract when compared with mast cell-containing littermates. Discussion Taken together, these data demonstrate that mast cells are reactive to Chlamydia spp. through multiple mechanisms that include TLR2-dependent pathways. Mast cells also play an important role in shaping in vivo immune responses in Chlamydia reproductive tract infection through both effector cell recruitment and modification of the chemokine microenvironment.